Pengaruh Teknik Relaksasi Otot Progresif untuk Penurunan Tingkat Nyeri pada Lansia dengan Gout Arthritis - Audrey Maurestha Kawile; Surianto; Matius Paundanan (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2025)
Progressive muscle relaxation technique is a relaxation therapy with movements that tighten and relax muscles at one time to provide a feeling of relaxation. This technique is one of the complementary therapies that can be given to help control and reduce the pain felt. The aim of this study was to analyze the impact of progressive muscle relaxation techniques to reduce the pain levels toward elderly with gouty arthritis in Pandere Public Health Center Working Area, by comparing pain levels before and after intervention to determine the effectiveness of this method in pain management. This type of research is quantitative using a pre-experimental design with a pre-test post-test design in one group (one group pre-test post-test). The sample in this study was 32 respondents with a sampling technique using purposive sampling. The results of the study showed that out of 32 respondents before theprogressive muscle relaxation technique was carried out, most respondents experienced moderate pain, and after the progressive muscle relaxation technique was carried out, most respondents experienced a decrease in pain levels to mild pain. The results of the Wilcoxon test obtained a p-value of 0.000 (p <0.05). There is an effect of progressive muscle relaxation techniques on reducing pain levels in the elderly with gout arthritis in the Pandere Health Center work area.